The mediating role of mindfulness in explaining the causal relationship between basic psychological needs and family functioning in firefighters - Mahdavi , Masoumeh; Rezakhani , Simindokht; Janangir , Pantea (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The purpose of this research was the mediating role of mindfulness in explaining the causal relationship between basic psychological needs and family functioning in firefighters. Method: The current research was applied in terms of purpose and descriptive and correlational in terms of method. The statistical population of the research included firefighters who were working in the fire department of Islamshahr, Baharestan and Rabat Karim cities in the winter of 2022 and spring of 2023, and they had at least two years of work experience in the fire department since their marriage. Based on the opinion of Hewitt and Kramer (2004), the research sample was estimated to be 240 people, which was increased to 300 people considering the possibility of attrition. The sampling method was non-random and available and voluntary. The measurement tools included Family Functioning Questionnaire (FAD), Basic Psychological Needs Questionnaire (BNSG-S) and Mindfulness Questionnaire (FFMQ). Data analysis was done through structural equation model method. Findings: The total path coefficient between basic psychological needs and family functioning (, )β=0.363) is significant and negative. Also, the path coefficient between mindfulness and family functionin )β=0.308) was negative and significant. The coefficient of direct path, )β=0.256) and indirect path (β=0.107) between basic psychological needs and family functioning was also negative and significant. Conclusion: It can be concluded that among firefighters, mindfulness negatively and significantly mediates the relationship between basic psychological needs and family functioning.